Problemy prawne i dylematy etyczne w badaniach autoetnograficznych w pedagogice resocjalizacyjnej - Ciechowska , Magdalena; Kusztal , Justyna (Studia Edukacyjne, 2021)
The aim of this article is to present and analyze the legal problems and ethical dilemmas of researchers studying difficult ways of life. There are a lot of questions about the ethical, acceptable and legal ways of research and in relation to the participants of the research. The practical aim of this article is to answer the question what we should do when we face different ethical dilemmas in our studies. A special difficult situation occurs to the researcher – pedagogue of social rehabilitation, because by conducting research on the phenomena of social exclusion or social pathology they describe and analyze situations related to crime, para-criminal behaviors, addictions, and provide profound diagnosis of disorders or therapy. During scientific research, the scholar penetrates the difficult situations, faces ethical dilemmas and encounters legal problems. Legal awareness and ethical responsibility are the guarantees of the pedagogue’s safety but above all the safety of the respondents. Although the article is not a complete and comprehensive study, it responds to the needs of researchers who themselves have to answer many questions about legal issues and solve many ethical dilemmas in the process of collecting and developing data.